Shu ju ke xue shi zhan shou ce di 2 ban = Practical data science cookbook : second edition / = Practical data science cookbook - Tattar, Prabhanjan 1979- (Ren min you dian chu ban she = Posts & Telecom Press, 2019)
Detailed summary in vernacular field only.
880-05;Ben shu zhong wen jian ti zi ban you Packt Publishing gong si shou quan ren min you dian chu ban she chu ban
Keywords: Object-oriented programming (Computer science); Data mining; Mathematical statistics -- Data processing; Python (Computer program language); R (Computer program language); Programmation orientée objet (Informatique); Exploration de données (Informatique); Statistique mathématique; Informatique; Python (Langage de programmation); R (Langage de programmation)